„Szkółka Niedzielna” pod redakcją ks. Tomasza Borowicza (1837-1849) i Ignacego Koteckiego (1849-1853) - Biesiada, Jacek (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
“Szkółka Niedzielna” (“The Sunday School”), a weekly published in Leszno from 1837 to 1853, was the first Polish journal for the peasantry. It was established on Dezydery Chłapowski’s initiative by Fr. Tomasz Borowicz, who was its first editor until mid-1849 (until the end of 1853 this function was performed by Ignacy Kotecki). Articles which appeared in the weekly not only urged readers to pursue school education but in themselves were a source of knowledge on religion, farming, horticulture, animal husbandry and veterinary medicine, also offering guidance on broadly understood country life (including among others such issues as household management, childcare, personal hygiene). Considerable space was allotted to anti-alcoholic texts. Financial difficulties caused the decline of “Szkółka Niedzielna”.